Estrategias de adaptación a la atención odontológica dirigido a niños diagnosticados con Trastorno Del Espectro Autista (TEA): Revisión Bibliográfica - Delgado Mosquera, Nataly Rashelle (2023)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that affects social interaction and communication skills, resulting in a lack of understanding and collaboration among children. Additionally, ASD encompasses a broad spectrum of sensory, visual, and olfactory manifestations that are characteristic of the condition, which can complicate dental care (DSM-5, 2013). The National Directorate of Disabilities of the Ministry of Public Health of Ecuador (2023) reported 2,955 individuals diagnosed with psychosocial disabilities. With the intention of raising awareness and gaining insight into sensory processing in children with ASD, and providing pertinent information to both dentists and parents or caregivers about dental care and healthy practices for maintaining oral health, the research question emerged: "To identify adaptation strategies for dental care that can be applied to children diagnosed with ASD." The specific objectives were to "Analyze the characteristics of orofacial sensory processing in children with Autism Spectrum Disorder (ASD) and design a dental care protocol tailored to children diagnosed with Autism Spectrum Disorder (ASD)." The study was descriptive and documentary, incorporating scientific articles in Spanish and English obtained from databases such as PubMed, Scielo, Medline, and BVS. The results underscore the significance of customizing treatment plans and how desensitization can foster cooperative patients and successful treatments, thereby reducing the need for pharmacotherapy, such as sedation, in dental care. It was concluded that children's behavior, orofacial sensory processing, and the severity of their autism spectrum disorder all play pivotal roles in determining the approach to care and the tools employed in treatment